Social dysfunction and depressive-like behaviour in an animal model of early Parkinson’s disease - Beatriz Lage Araujo Schweizer (2024)
Depressive symptoms, which can include anhedonia, are common nonmotor changes in Parkinson’s disease (PD). Social dysfunction is also observed in PD patients, either independently or in association with depression or other neuropsychiatric disorders. These nonmotor changes may be present at the time of, or even before, the onset of the cardinal motor symptoms. Treating nonmotor symptoms, particularly in the very early stages of the disease, can have a positive impact on the patient’s quality of life and the disease’s prognosis. However, little is known about their underlying mechanisms and their association with other symptoms, resulting in a lack of effective interventions. The loss of dopaminergic neurons in the substantia nigra pars compacta (SNc) and their terminals within the dorsal striatal region is a key feature of PD and may be sufficient to induce nonmotor symptoms early in the disease. To test this hypothesis, rats with a partial bilateral lesion within the dorsolateral striatum were assessed for behaviours associated with anhedonia and social dysfunction. The lesion was induced by infusion of 6-hydroxydopamine (6-OHDA), following a previously described method for generating a model of early PD. The animals underwent the sucrose preference test (in the first- and third-week post-lesion) and the social interaction test (in the third week post-lesion). Assessment of motor function was also conducted (in the third- and fourth-week post-lesion) using the footprint and open field test. Hedonic deficits were only apparent in the first week following the lesion, but not in the third. The 6-OHDA group showed a significant reduction in social behaviour. No gross motor impairments in locomotion or gait that could confound the results were observed at either of the two time-points investigated. The changes in social behaviour may reflect an impairment of motivated behaviour, dependent on frontal-striatal circuits, or dysfunction in other regions associated with both social behaviours and depressive symptoms, that might be impaired as a result of dysfunction in the nigrostriatal system (i.e. limbic system). Overall, the results suggest that the early impairment in the nigrostriatal pathway is sufficient to induce changes in social behaviour, which could reflect the behaviour of social withdrawal observed in PD patients. Future studies should investigate whether this model also exhibits behavioural changes associated with other non-motor symptoms commonly observed in PD patients, such as changes in the sleep/wake cycle and cognitive impairment in executive functions.